Development of an Augmented Reality (AR) app for NTU learning trail - Ho, Kok Wee (2019)
The NTU Learning Trail brings visitor through the NTU campus, beginning at the Jalan Bahar entrance and ending at the hive. The NTU Learning trail is designed to introduce NTU and its respective colleges, schools and autonomous institutions present within its campus to the many local and foreign visitors. As NTU expects many visitors daily, the Learning Trail was conceptualised to maximise the visitor experience to embrace and appreciate the success and achievements of NTU and its respective colleges and schools. To enhance the NTU Learning trail, a mobile application for visitors is developed with the integration of Augmented Reality (AR). The use of AR as part of a learning trail introduces the interaction between the physical location and the app user. An AR app creates the possibility to enhance visitor experience and provide direct and succinct information through proper planning of the User Experience/User Interface (UX/UI). With a human guide, the additional interactive element will improve the visitor experience and leave a positive impression. Similarly, the visitor could be exploring NTU without a human guide, navigating the NTU campus with ease and leaving NTU with a positive impression.